An Atypical Late Embryogenesis Abundant Protein OsLEA5 Plays a Positive Role in ABA-Induced Antioxidant Defense in Oryza sativa L. (7th February 2018) - Huang, Liping; Zhang, MengYao; Jia, Jing; Zhao, Xixi; Huang, Xingxiu; Ji, E; Ni, Lan; Jiang, Mingyi
Abstract: OsLEA5 acts as a co-regulator of a transcriptional fact ZFP36 to enhance the expression and the activity of ascorbate peroxidase OsAPX1 to regulate seed germination in rice, but it it unknown whether OsLEA5 is also crucial in plant seedlings under stress conditions. To determine this, we generated OsLEA5 overexpression and knockdown rice plants. We found that overexpression of OsLEA5 in rice plants enhanced the tolerance to drought and salt stress; in contrast, an RNA interference (RNAi) mutant of OsLEA5 rice plants was more sensitive to drought and salinity. Further investigation found that various stimuli and ABA could induce OsLEA5 expression, and OsLEA5 acted downstream of ZFP36 to be involved in ABA-induced generation of hydrogen peroxide (H2 O2 ), and the regulation of the expression and the activities of antioxidant defense enzymes in plants leaves, and OsLEA5 contributed to stabilize ZFP36. Additionally, OsLEA5 participates in the accumulation of ABA by up-regulating ABA biosynthesis genes and down-regulating ABA metabolism genes. Moreover, we found that two homologs of OsLEA5 (5C700, short for Os05g0526700; and 5C300, short for Os05g0584300) which were induced by ABA also interacted with ZFP36 separately; interestingly, the nuclear-located 5C700 could also act as a co-activator of ZFP36 to modulate OsAPX1, while 5C300 which was down-regulated by ABA induction acted as an ABA-induced inhibitor of ZFP36 to regulate OsAPX1 . Hence, our conclusion is that OsLEA5 participates in the ABA-mediated antioxidant defense to function in drought and salt stress response in rice, and the 5C subgroup of LEAs contribute by acting as co-regulators of the transcription factor ZFP36.